2019
DOI: 10.15408/kauniyah.v12i1.8972
|View full text |Cite
|
Sign up to set email alerts
|

PERTUMBUHAN DAN KANDUNGAN POLIFENOL TANAMAN KATUK (Sauropus androgynus (L.) Merr) PADA MEDIA TANAM DENGAN PEMBERIAN ASAM HUMAT

Abstract: AbstrakKatuk (Sauropus androgynus (L.) Merr) merupakan tanaman sayuran yang berkhasiat obat karena mengandung senyawa aktif diantaranya flavonoid, steroid, dan tanin yang digunakan sebagai antioksidan. Peningkatan pertumbuhan tanaman dapat dilakukan dengan meningkatkan produksi biomassa tanaman, yang diharapkan  dapat meningkatkan kandungan senyawa aktif pada tanaman seperti polifenol. Penggunaan asam humat dapat meningkatkan kualitas media tanaman sehingga pertumbuhan tanaman dapat meningkat. Tujuan penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…On that condition, the polyphenols are oxidized by the phenylalanine ammonia-lyase (PAL) enzyme through the phenolic pathway. This activity causes plants to become more resistant [5]. This hypothesis can explain that the polyphenols which synthesized by iodine and potassium are lower than other minerals.…”
Section: Fig 2 Decrease Incidence Of Rust In Lowland Arabica Coffeementioning
confidence: 99%
“…On that condition, the polyphenols are oxidized by the phenylalanine ammonia-lyase (PAL) enzyme through the phenolic pathway. This activity causes plants to become more resistant [5]. This hypothesis can explain that the polyphenols which synthesized by iodine and potassium are lower than other minerals.…”
Section: Fig 2 Decrease Incidence Of Rust In Lowland Arabica Coffeementioning
confidence: 99%
“…Exogenous antioxidants can be obtained from nature, primarily from plants. Polyphenolic compounds, specifically flavonoids found in plants, can be employed as exogenous antioxidants for the body (Proklamasiningsih et al, 2019). In a study conducted by Silva et al, it was demonstrated that the flavonoid catechin can preserve the motility of frozen goat sperm (Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are compounds with multiple phenol groups that contribute to the prevention of degenerative ailments and cardiovascular disorders. These polyphenolic compounds can be classified into two distinct categories: flavonoids ( flavones, flavanols, flavanones, isoflavones, anthocyanidins, and chalcones) and tannins ( phenolic acid polymers, catechins, and isocatechins) (Proklamasiningsih et al, 2019).…”
Section: Introductionmentioning
confidence: 99%